Pediatric Chest Ultrasound for Bedside Diagnosis of Pneumonia: A Validation Study for Diagnostic Options in Developing Countries - Christine W.S. Basanti; Magd A. Kotb; Hadeel M. Seif; Fayez I. Farag; Azza K. Abdelmegeid (Cairo University, Faculty of Medicine, Department of Pediatrics, 2021)
Background: Pneumonia remains a major cause of morbidity and mortality in childhood with a higher burden in developing countries. Diagnosis relies on clinical findings with supporting evidence from chest X-ray (CXR) and occasionally chest computed tomography (CT). Aim of the work: The aim of this study was to assess the role of lung ultrasonography (LUS) for bedside diagnosis of pediatric pneumonia in comparison to chest CT as a gold standard. Methods: The study was performed on 50 children admitted to Cairo University Children's Hospitals. All children presented with the classical clinical picture of pneumonia and did CXR, LUS and chest CT. Results: Radiological findings demonstrated lung consolidation in 48 patients (96%) by CXR, 49 (98%) patients by LUS and all 50 patients (100%) by CT chest. Pleural effusion was found in 8 (16%) patients by CT chest, all of which were detected by LUS (100%), but only 5 were correctly detected by CXR (specificity 62.5%) in addition to 3 false positive cases. LUS detected pleurisy in 29 children (58%) (specificity 100%) while X-rays did not. Also 70% of children needed sedation before CT scanning as compared to none for LUS. Conclusion: Lung ultrasound is a sensitive, specific, safe and available tool that can be used by clinicians in cases of suspected pneumonia. It is more reliable than CXR, does not require sedation, and can be repeated at the patient's bedside with no risk of irradiation.